2021
DOI: 10.7717/peerj.11992
|View full text |Cite
|
Sign up to set email alerts
|

Reef manta rays forage on tidally driven, high density zooplankton patches in Hanifaru Bay, Maldives

Abstract: Manta rays forage for zooplankton in tropical and subtropical marine environments, which are generally nutrient-poor. Feeding often occurs at predictable locations where these large, mobile cartilaginous fishes congregate to exploit ephemeral productivity hotspots. Investigating the zooplankton dynamics that lead to such feeding aggregations remains a key question for understanding their movement ecology. The aim of this study is to investigate the feeding environment at the largest known aggregation for reef … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…and prey abundance (Notarbartolo-di-Sciara, 1988;Anderson et al, 2011;Jaine et al, 2012;Stevens, 2016;Hacohen-Domenéet al, 2017;Stewart et al, 2017b;Lezama-Ochoa et al, 2019b;Lezama-Ochoa et al, 2020;Harris and Stevens, 2021). In the most closely studied example of large feeding aggregations (M. alfredi), no cooperative grouping behavior was observed (Stevens, 2016;Murray, 2019;Armstrong et al, 2021), indicating that these feeding aggregations are likely site-specific behaviors in which prey availability and site characteristics lead to local enhancement of prey (Silverman et al, 2004;Jourdain and Vongraven, 2017). The co-occurrence of multiple individuals, with prey availability likely also determining the group size (Murray, 2019).…”
Section: Feeding Aggregationsmentioning
confidence: 99%
See 2 more Smart Citations
“…and prey abundance (Notarbartolo-di-Sciara, 1988;Anderson et al, 2011;Jaine et al, 2012;Stevens, 2016;Hacohen-Domenéet al, 2017;Stewart et al, 2017b;Lezama-Ochoa et al, 2019b;Lezama-Ochoa et al, 2020;Harris and Stevens, 2021). In the most closely studied example of large feeding aggregations (M. alfredi), no cooperative grouping behavior was observed (Stevens, 2016;Murray, 2019;Armstrong et al, 2021), indicating that these feeding aggregations are likely site-specific behaviors in which prey availability and site characteristics lead to local enhancement of prey (Silverman et al, 2004;Jourdain and Vongraven, 2017). The co-occurrence of multiple individuals, with prey availability likely also determining the group size (Murray, 2019).…”
Section: Feeding Aggregationsmentioning
confidence: 99%
“…These mobulid feeding aggregations can be influenced by zooplankton size, species, and concentration. For example, in Hanifaru Bay, Maldives, Armstrong et al (2021) found that M. alfredi formed feeding aggregations when the zooplankton community was dominated by large crustaceans (copepods) and total biomass was greater than a theoretical prey density threshold for net energy gain (25.2 mg m 3 ). At this feeding aggregation site, the foraging opportunities appeared to occur when strong lunar tides overcame the force of the prevailing monsoonal current, drawing plankton-rich water from deep waters outside the atoll into the shallow reef inlet (Harris and Stevens, 2021) attracting up to 250 M. alfredi individuals (Stevens, 2016;Harris et al, 2020) (Table 2).…”
Section: Feeding Aggregationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manta rays (Family Mobulidae) are pelagic planktivores that aggregate in regions supporting high zooplankton densities and cleaning stations, where symbiotic fish remove parasites from them (Feder, 1966;Couturier et al, 2012;Stevens, 2016;White et al, 2017). Being large filter feeders, manta rays spend their lives in proximity to where plankton blooms occur, these being elicited by temporal and spatial environmental cues (Sims et al, 2005;Armstrong et al, 2021). The great variability and transience of regional plankton likely drive their foraging behavior, prey sources, and habitat use (Stewart et al, 2017;Barr and Abelson, 2019;Putra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Mobula alfredi predictably migrate across the archipelago following areas of enhanced zooplankton availability, driven by the biannual reversal of the South Asian Monsoon winds (Anderson et al, 2011b;Harris et al, 2020). Aggregations of M. alfredi occur at locations where food becomes seasonally abundant, often in shallow bays and channels (Armstrong et al, 2016(Armstrong et al, , 2021aHarris et al, 2020). They also visit nearby cleaning stations where cleaner fishes remove parasites and clean wounds (Foster, 1985;Marshall, 2008), and where courtship and mating interactions occur (Stevens, 2016;Stevens et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%